A synopsis of Anthoxanthum (Poaceae: Pooideae: Poeae) in southern Africa and description of a new subspecies. Issue 2 (June 2016) - Mashau, Aluoneswi
Summary A new subspecies ofAnthoxanthum (Pooideae: Poeae) from South Africa was identified, described, illustrated and compared with similar members of the genus.